The formation of tubular seep carbonate deciphered from mineralogical and geochemical characteristics: an example from the South China Sea - Wei, Jiangong; Miao, Xiaoming; Gan, Kailong; Li, Jiangtao; Li, Jiwei; Liu, Xiting; Xu, Hengchao; Chen, Shun; Ta, Kaiwen; Wan, Zhifeng; Wu, Tingting (Frontiers in Marine Science, 2024)
As a special type of seep carbonate, the many details concerning the formation mode and mechanism of tubular seep carbonates are rarely reported. Here, new geochemical and mineralogical data regarding tubular seep carbonate (SQW-65) are reported. Sample SQW-65 had anomalously negative δ13C values and positive δ18O values, which suggested the dissociation of gas hydrate. Additionally, almost all the sub-samples showed no Ce anomaly (Ce/Ce*average = 0.93), with obvious U enrichment (21.3< UEF <240.3), which indicates that the studied tubular seep carbonate was formed in an anoxic environment. Subsequently, the formation process of the studied tubular seep carbonate is further discussed according to the variability of mineralogical and geochemical characteristics from the rim to the core of the tubular formation. In the early stage of the studied tubular seep carbonate (periphery), owing to the influence of terrigenous components, the quartz and Ti content and Y/Ho ratio were high. However, with the formation of the periphery, the influence of terrigenous components was gradually weakened. In addition, from the rim to the core, the carbon and oxygen isotope values showed a “covariation” coupling relationship, an enrichment of U, and a reduction in total rare earth element content. This is because as the outer wall thickens and the internal fluid channel narrows, the intensity of the sulphate-driven anaerobic oxidation of methane and the associated precipitation rate of carbonate also increase.